Rancangan Penyuluhan Pertanian Pengendalian Ulat Grayak (Spodoptera Frugiperda) pada Tanaman Jagung dengan Menggunakan Pestisida Nabati di Simalungun - Jamarkos Purba; Mukhlis Yahya; Amelia Zuliyanti Siregar (AGRIFITIA : Journal of Agribusiness Plantation, 2026)
The armyworm pest is one of the main problems in corn cultivation in Silou Kahean District, Simalungun Regency, Nortern Sumatera. Farmers' lack of understanding of environmentally friendly control methods has led to the continued high use of pesticides. This study aims to: (1) identify the potential areas for agricultural extension, (2) analyze the objectives of extension activities on armyworm control using botanical pesticides, (3) analyze the objectives of extension activities based on farmers' socio-economic characteristics, (4) assess farmers' acceptance of extension activities, and (5) determine farmers' acceptance of the extension program design. The research method used is quantitative descriptive with data collection techniques through questionnaires and interviews. The research was conducted from April to June 2024 and calculated using a rating scale. The results showed that the extension targets were corn farmers who were members of farmer groups. The material provided focused on the use of botanical pesticides in controlling grayak caterpillars. The media used were brochures and caterpillar samples, with methods including lectures, discussions, and compression. The extension activities were conducted three times at the extension service post and on farmers' land. The conclusion indicates that the extension activities were well received by farmers and deemed beneficial in supporting more sustainable agricultural practices. Keywords: Extension program design; farmers; gray caterpillars; corn; botanical pesticides.     ABSTRAK Hama ulat grayak merupakan salah satu permasalahan utama dalam budidaya jagung di Kecamatan Silou Kahean, Kabupaten Simalungun, Sumatera Utara. Kurangnya pemahaman petani terhadap metode pengendalian yang ramah lingkungan menyebabkan masih tingginya penggunaan pestisida. Penelitian ini bertujuan untuk: (1) mengidentifikasi potensi wilayah penyuluhan pertanian, (2) menganalisis tujuan penyuluhan pengendalian ulat greyak dengan pestisida nabati, (3) menganalisis tujuan penyuluhan berdasarkan karakteristik sosial dan ekonomi petani, (4) menilai tingkat penerimaan petani terhadap kegiatan penyuluhan, dan (5) mengetahui penerimaan petani terhadap rancangan penyuluhan yang disusun. Metode penelitian yang digunakan adalah deskriptif kuantitatif dengan teknik pengumpulan data melalui kuesioner dan wawancara. Penelitian dilaksanakan pada bulan April hingga Juni 2024 dan dihitung menggunakan skala penilaian. Hasil penelitian menunjukkan bahwa sasaran penyuluhan adalah petani jagung anggota kelompok tani. Materi yang diberikan fokus pada penggunaan pestisida nabati dalam pengendalian ulat greyak. Media yang digunakan berupa brosur dan contoh ulat, dengan metode ceramah, diskusi, dan kompresi. Kegiatan penyuluhan dilakukan sebanyak tiga kali di pos layanan penyuluhan dan lahan petani. Simpulan penelitian menunjukkan bahwa penyuluhan diterima dengan baik oleh petani dan dinilai bermanfaat dalam mendukung praktik pertanian yang lebih berkelanjutan. Keywords: Rancangan penyuluhan; petani; ulat grayak; jagung; pestisida nabati.